Ambiência e manejo de espera pré-abate de suínos em condições de clima tropical: influência nos indicadores termofisiólogicos e de qualidade da carne - Viveiros, Kilvia Karoline de Souza (2022)
Inadequate pre slaughter handling and heat stress can compromise the welfare and physiology of pigs, especially in tropical climates. Thus, this study aimed to evaluate the conditions of unloading, waiting, and slaughtering operations on a commercial scale, and in a slaughterhouse in the municipality of Aquiraz, Ceará, Brazil. A database with information about origin, travel time, and pre transport handling on t he farms was obtained by questionnaires applied to the drivers responsible for the loads. Twelve lots ranging from 30 to 100 animals were evaluated, and 60 pigs weighing 107 ± 5.0 kg were sampled and distributed in three groups according to transport time (TT), unloading time (DT), and waiting time to slaughter (TE). On the arrival of the animals and 30 minutes before slaughter, the surface temperature, respiratory rate, and rectal temperature of the pigs were measured. Environmental monitoring was performe d by means of mini weather stations. Meat pH data were collected 45 minutes after slaughter from the loin and shoulder. Data were subjected to ANOVA, correlation, and multivariate analysis. The first two components explained 97% of the treatments, where it was possible to verify the influence of management and thermal stress of the facilities on the physiological variables of the pigs and meat quality indicators. Discriminant analysis showed that group C presented multivariate differences in relation to the others, especially for the variables rectal temperature before slaughter, respiratory rate and rectal temperature on arrival at the slaughterhouse. The TT, TD, number of employees and number of animals unloaded at the same time, negatively affected the ph ysiology and meat quality, causing a tendency of DFD defects in the shoulder and PSE in the loin. Furthermore, it was observed that the longer the time to unload the animals, the more aggressive handling was used. Based on the variables respiratory rate an d enthalpy, it can be evidenced that most animals were affected by stress, caused by heat, which resulted in loss of welfare during the stay in the waiting environment and meat quality, leading to DFD defects on the pallet. However, in some analyses, anima ls with hypothermia were observed. This result may be associated with the environmental conditions and intensified by the practice of wetting adopted by the slaughterhouse and due to.